Humanities, social and theological sciences and the challenges of social impact and commercialization. Suggestions for the scientific discipline of canon law - Słowikowska , Anna (Prawo Kanoniczne, 2024)
The article undertakes an analysis of the challenges facing the humanities, social sciences and theological sciences in the context of increasing pressure to commercialize research results and the requirements to demonstrate so-called social impact. The discipline of canon law, which – due to its ecclesiastical nature and the subject of its research – finds itself on the boundary between the requirements of state law regarding the transfer of knowledge to the economy and its mission to serve the community of the Church and society, has a special place here. The author points out that the socio-economic environment for canonical science is both ecclesiastical institutions (curiae, ecclesiastical tribunals, institutes of consecrated life) and secular institutions (state courts, law firms), which expect expert opinions and advice. The article critically assesses the phenomenon of subordinating scientific activity to the rules of the market, pointing out the danger of reducing the search for truth to measurable economic effects. It also indicates calls for action, including the creation of networks of universities and canonical law firms, the development of consulting services and the implementation of the concept of service learning as a means of realizing social impact. The text is a voice in the discussion of how to reconcile the specifics of ecclesiastical sciences with the requirements of state law on the commercialization of research.